Cognitive Aspects of Teacher Expertise in ELT - Elham Yazdanmehr; Ramin Akbari (Journal of English Language Teaching and Learning, 2015)
The present paper seeks to investigate the cognitive abilities of expert EFL teachers. To this aim, the existing literature was examined and ten cognitive themes were derived which were further investigated through interviews conducted with ten academics, teacher trainers and exemplary teachers of the field in the Iranian context. The ten extracted themes were attested by interviewees’ comments. They include: fast pattern recognition, selective attention, holistic perception, superior memory, fast information encoding, anticipation power, perception of teacher’s role, awareness of situation-specific class events, awareness of their knowledge, linking prior and new knowledge. These themes are further explained and discussed along with extracts of the actual interviews. It is recurrently reminded that these cognitive issues are just one aspect of teaching expertise in ELT and the whole idea is part of a model of expertise being constructed which consists of 8 factors only one of which is teacher cognition.